Franco and the Spanish Civil War - Meneses, Filipe Ribeiro de, 1969- 1969- (Introductions to history, 2001)
"Franco and the Spanish Civil War is a wide-ranging and insightful analysis of the origins, course and consequences of the conflict and of Franco's role within it. It offers a broad view of the war through a survey of its social and cultural, as well as its military and political dimensions. In particular, it traces Franco's meteoric rise to power, his conduct of the war, and his long subsequent rule." "This introduction illuminates the many different interpretations of the conflict by examining a variety of perspectives. Franco and the Spanish Civil War places the war in its national and global contexts, exploring both nationalist and republican points of view, and giving attention to foreign participation in the conflict. It provides an accessible and well-rounded starting point for any student of the subject."--BOOK JACKET.